2009
DOI: 10.1200/jco.2008.20.5104
|View full text |Cite
|
Sign up to set email alerts
|

Margin Clearance and Outcome in Resected Pancreatic Cancer

Abstract: These data demonstrate that a margin clearance of more than 1.5 mm is important for long-term survival in a subgroup of patients. More aggressive therapeutic approaches that target locoregional disease such as radiotherapy may be beneficial in patients with close surgical margins. Stratification of patients for entry onto future clinical trials based on this criterion may identify those patients who benefit from adjuvant radiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
194
3
10

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 295 publications
(222 citation statements)
references
References 29 publications
15
194
3
10
Order By: Relevance
“…4) using a univariate Cox analysis of overall survival (SI Materials and Methods), whereas low staining for GNAQ showed a borderline significant association with poor survival (P = 0.051). Analysis of CTNND1 staining in a second independent pancreatic cancer tissue microarray of 142 patient samples (44,45) confirmed that decreased CTNND1 is significantly associated with poor survival in pancreatic cancer patients who underwent operative resection (Fig. S3).…”
Section: Ccgs In Sb-driven Pancreatic Cancer Predict Human Pancreaticmentioning
confidence: 92%
“…4) using a univariate Cox analysis of overall survival (SI Materials and Methods), whereas low staining for GNAQ showed a borderline significant association with poor survival (P = 0.051). Analysis of CTNND1 staining in a second independent pancreatic cancer tissue microarray of 142 patient samples (44,45) confirmed that decreased CTNND1 is significantly associated with poor survival in pancreatic cancer patients who underwent operative resection (Fig. S3).…”
Section: Ccgs In Sb-driven Pancreatic Cancer Predict Human Pancreaticmentioning
confidence: 92%
“…In der aktuellen Literatur werden Sicherheitsabstände von 1, 5 oder sogar 10 mm zum Resektionsrand als R0 angegeben [5,6,8,10]. Während in der aktuellen TNMDefinition der R1-Status als mikroskopischer Tumorzellnachweis am CRM festgelegt ist [4], empfiehlt das Royal College of Pathologists einen minimalen Tumor- Abb.…”
Section: » Ein Konsens Hinsichtlich Der Definition Des R-status Beim unclassified
“…R0-resezierte Pankreaskarzinome könnten beispielsweise als CRM-positiv klassifiziert werden, wenn der Abstand der Tumorzellen zum Resektionsrand weniger als 1 mm oder 1,5 mm betrifft. Die Frage, welcher Abstand zum [16].…”
unclassified